for the first one..
y = x/ln(x)
alright, so, quotient rule states:
(u'v - v'u)/(v^2)
let u = x, and v = ln(x)
and keep in mind that the derivative of ln(x) = 1/x
give that a shot
for the second one,
square root (sin(x) + cos(x)) can be written as..
(sinx + cosx)^(1/2)
using the chain rule,
(1/2)[(sinx + cosx)^(-1/2)] (cos(x) - sin(x))
keeping in mind that the derivative of sinx = cosx, and the derivative of cosx = -sinx.
the third one I'm not really sure what you meant by it, so, try to clarify hehe